First subsurface characterization of periglacial areas in the Yendegaia National Park, Southern Tierra del Fuego Island, Chile - Alberto Carrera; Mirko Pavoni; Sebastian Ruiz-Pereira; Jacopo Boaga; Luca Peruzzo; Viola Cioffi; Pawel Michal Slupski; Carlos Marquardt; Levente Ivan; Gergely Boros; Zoltan Szalai; Balazs Nagy (Cold Regions Science and Technology, 2026)

DataPix4: A C++ framework for Timepix4 configuration and read-out - Viola Cavallini; Nicolò Vladi Biesuz; Riccardo Bolzonella; Enrico Calore; Massimiliano Fiorini; Alberto Gianoli; Xavier Llopart Cudie; Sebastiano Fabio Schifano (Computer Physics Communications, 2025)

A daily time-step hydrological-energy-biomass model to estimate green roof performances across Europe to support planning and policies - Emanuele Quaranta; Ciril Arkar; Cristina Branquinho; Elena Cristiano; Ricardo Cruz de Carvalho; Michal Dohnal; Ilaria Gnecco; Dominik Gößner; Vladimira Jelinkova; Carmelo Maucieri; Milena Mohri; Panayiotis A. Nektarios; et al. (Urban Forestry & Urban Greening, 2024)

Underwater Noise Monitoring with Real-Time and Low-Cost Systems, (The CORMA Experience) - Paolo Diviacco; Antonio Nadali; Massimiliano Iurcev; Mihai Burca; Rodrigo Carbajales; Matteo Gangale; Alessandro Busato; Fabio Brunetti; Lorenzo Grio; Alberto Viola; Nikolas Potleca (Journal of Marine Science and Engineering, 2021)
Marine life can be severely affected by anthropogenic underwater noise. This latter increased proportionally to the rise of human activities such as maritime traffic, marine civil engineering works, oil- and gas-related activities or offshore wind farms; so much so that, currently, it can be considered a threat to the environment. Assessing underwater noise requires quite some investments both in personnel and instrumentation. If this is affordable by several governmental and scientific organizations, this cannot be extended straightforwardly to all research initiatives or to developing countries. In addition, time and geographic coverage of monitoring can also be significantly limited by the costs of multiple installations. We explore the possibility to use a solution based on off-the-shelf and low-cost technologies combined with a scalable infrastructure developed with open-source tools only. The perspective to avoid proprietary solutions allows great flexibility in extending the current paradigm toward real-time transmission, processing, and web-based data access. Our solution has been deployed at sea in November 2020 and is providing data continuously ever since. First results from the analysis of these data allowed us to highlight several interesting abiotic and anthropogenic temporal patterns.

MDA-MB-231 breast cancer cell viability, motility and matrix adhesion are regulated by a complex interplay of heparan sulfate, chondroitin−/dermatan sulfate and hyaluronan biosynthesis - Manuela Viola; Kathrin Brüggemann; Evgenia Karousou; Ilaria Caon; Elena Caravà; Davide Vigetti; Burkhard Greve; Christian Stock; Giancarlo De Luca; Alberto Passi; Martin Götte (Glycoconjugate Journal, 2017)

Adaptation of water resources systems to changing society and environment: a statement by the International Association of Hydrological Sciences - Serena Ceola; Alberto Montanari; Tobias Krueger; Fiona Dyer; Heidi Kreibich; Ida Westerberg; Gemma Carr; Christophe Cudennec; Amin Elshorbagy; Hubert Savenije; Pieter Van Der Zaag; Dan Rosbjerg; et al. (Hydrological Sciences Journal, 2016)

Biology and biotechnology of hyaluronan - Manuela Viola; Davide Vigetti; Evgenia Karousou; Maria Luisa D’Angelo; Ilaria Caon; Paola Moretto; Giancarlo De Luca; Alberto Passi (Glycoconjugate Journal, 2015)

A Statistical Approach to the Validation and Optimisation of Geoheritage Assessment Procedures - Viola María Bruschi; Antonio Cendrero; Juan Antonio Cuesta Albertos (Geoheritage, 2011)